Respuesta del cultivo de maíz (Zea mays L) a la aplicación de abonos foliares a base de algas marinas. - Ubilla Figueroa, Luisiño Santiago (2017)
Seaweed-based foliar fertilizers have been shown to raise the production levels of some crops, therefore, the present investigation was carried out in order to evaluate the response of the corn crop to the application of foliar fertilizers based on marine algae. The trial was established on land of the "Diana Marisol" farm, at Km. 10.5 of the Quevedo-Santo Domingo road, Rcto. Four Sleeves between the coordinates 0 ° 55'51.1 "S 79 ° 29'18.3" W, a height of 60 m.s.n.m. The simple corn hybrid Nidera NS-8282 distributed by the company El Agro was used as genetic material. The Complete Random Blocks Design was applied with 7 treatments in 3 repetitions, with a total of 21 experimental plots. The treatments studied were: T1: 600 g/ha of Agrostemin, T2: 400 g/ha of Agrostemin, T3: 200 g/ha of Agrostemin, T4: 1.5 l/ha of Basfoliar Algae, T5: 1.0 l/ha of Basfoliar Algae, T6: 0.5 l/ha of Basfoliar Algae and T7: Control without foliar fertilization. The main results show that the plants showed a greater growth when sprinkled with 1.5 l/ha of Basfoliar reaching an average height of 235.7 cm at the time of harvest, harvesting larger ears, diameter and number of rows of seeds , registering values of 17.5 cm, 5.6 cm and 15.8 rows of seeds, in their order, and in turn more heavy cobs with 275.0 g, with a net weight of seeds of 235.4 g. Allying 1.5 l/ha of Basfoliar algae, higher grain yield per hectare was obtained with 7310.3 Kg. The highest economic benefit was obtained when applying 1.5 l/ha of Basfoliar algae, reflecting a benefit/cost ratio of 1.42 (42% profitability). Key words: foliar fertilization, seaweed, maize